Pengaruh Media Papan Cerita Terhadap Hasil Belajar Bahasa Indonesia Siswa Sekolah Dasar - Eka Yulianti; Mulya Yusnarti; Hasan; Sumiyati; Farah Wahidah (CV. Gerasi Insan Nusantara, 2026)
This research is motivated by the conventional instructional methods in elementary schools that rely heavily on traditional media, resulting in low student engagement and suboptimal learning outcomes in Indonesian language learning. This study aims to examine the empirical effect of storyboard media on the Indonesian language learning outcomes of fifth-grade elementary school students. Utilizing a quantitative approach with a pre-experimental one-group pretest-posttest design, this research involved 19 students as the sample. Data were collected using learning outcome tests and analyzed using parametric inferential statistics. The normality test (Shapiro-Wilk, p > 0.05) and the homogeneity test (Levene's, p > 0.05) confirmed that the data were normally distributed and homogeneous. The hypothesis testing using the Paired Samples T-Test yielded a significance value (p-value) of 0.000, which is lower than the significance level of 0.05 (p < 0.05). This result indicates a statistically significant difference between the pretest and posttest scores. Therefore, it can be concluded that the implementation of storyboard media exerts a significant positive effect on the Indonesian language learning outcomes of fifth-grade elementary school students, thereby rejecting H0 and accepting Ha.